2015
DOI: 10.1016/j.celrep.2015.10.058
|View full text |Cite
|
Sign up to set email alerts
|

Dectin-1 Regulates Hepatic Fibrosis and Hepatocarcinogenesis by Suppressing TLR4 Signaling Pathways

Abstract: Summary Dectin-1 is a C-type lectin receptor critical in anti-fungal immunity but Dectin-1 has not been linked to regulation of sterile inflammation or oncogenesis. We found that Dectin-1 expression is upregulated in hepatic fibrosis and liver cancer. However, Dectin-1 deletion exacerbates liver fibro-inflammatory disease and accelerates hepatocarcinogenesis. Mechanistically, we found that Dectin-1 protects against chronic liver disease by suppressing TLR4 signaling in hepatic inflammatory and stellate cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 49 publications
3
75
0
Order By: Relevance
“…Finally, Miller and coworkers (154,155) recently demonstrated an unexpected inhibition of TLR4-dependent inflammatory cytokine expression by the CLR Dectin-1 and Mincle (Fig. 4C).…”
Section: Conflicting Signaling Of Clrs: Negative Regulationmentioning
confidence: 75%
See 1 more Smart Citation
“…Finally, Miller and coworkers (154,155) recently demonstrated an unexpected inhibition of TLR4-dependent inflammatory cytokine expression by the CLR Dectin-1 and Mincle (Fig. 4C).…”
Section: Conflicting Signaling Of Clrs: Negative Regulationmentioning
confidence: 75%
“…4C). First, they observed that Dectin-1-deficient mice showed more hepatic fibrosis in a model of liver inflammation (154). Similarly, Mincle-deficient mice were more susceptible to endotoxic shock than were wild-type controls, resulting in higher mortality and elevated cytokine levels (155).…”
Section: Conflicting Signaling Of Clrs: Negative Regulationmentioning
confidence: 99%
“…In this study, we again confirmed higher CCL2 expression in keratinocytes from OLP patients, compared with that of control subjects, which was reported in our recent study. A few studies demonstrated that TLR‐4‐induced CCL2 overproduction in podocytes, macrophages, hepatic stellate cells, gingival epithelial cells, and even lung cancer cells . In these studies, LPS or another PAMP ligand induced TLR‐4 expression via an independent NF‐κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Dectin-1 also enhances NK-dependent tumor cell killing by recognizing the N-glycan structures of some cancer cells and activating IRF5 [136]. It has also recently been reported that Dectin-1 protects against liver fibroinflammatory disease and hepatocarcinogenesis by inhibiting TLR4 signaling [137]. However, the association between cancer and Dectin-2, another important CLR, has not been extensively investigated.…”
Section: Clr Signaling In Cancermentioning
confidence: 96%